Analysis of archival appraisal in the Office of the Secretary to the Sangguniang Panlalawigan (Provincial Council) in Eastern Visayas (Region 8) - Fumar, Florabel M. (University of the Philippines Diliman, 2014)
The archival appraisal practices in the Office of the secretary to the Sangguniang Panlalawigan in Eastern Visayas were determined using a questionnaire and an informal interview. Five out of six personnel-in-charge of archival appraisal from the six provinces particiipated in this study. Results suggested that: (1) the personnel-in-charge of archival appraisal held different positions in the organization who perceived it as just one of their tasks; (2) knowledge on archival theories was considered most essential for archival appraisal which could be best acquired through training/workshops; (3) they used functonal analysis, use analysis, precedents, and accessibility to users, and at times, the Jenkinsonian approach in archival appraisal though these were not guarantees that archival records were always selected; (4) not enough appraisal guidelines and administrative support were mostly affecting their capabilities to do archival apraisal. They recommended that more support from within and among institutions, better understanding of records, application of information technology, guidelines or standards, more comprehensive policies and procedures, workshops and courses on archives could help them improve their local archival appraisal. The researcher recommended that they should come up with their own Records Disposition Schedule using the macro approach with emphasis on the context of records creation during appraisal.